2007
DOI: 10.1007/s10903-007-9036-z
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Knowledge about Asthma Between Asians and Non-Asians at Two Pediatric Clinics

Abstract: Little is known about the relative knowledge of asthma in recent immigrant Asian populations in the United States (US). To comparatively assess asthma knowledge for Asian and non-Asian populations, 333 parents and children were surveyed at two geographically close urban clinics that had a large percentage of Asian patients, most of whom were Chinese. The Asian respondents scored lower compared to the non-Asian respondents on 4 of the 6 knowledge questions (p < 0.001). Subcategories of non-Asians (white, Africa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…15 Other studies also found a higher burden of asthma among AI/AN and/or Filipino children, with multiple underlying socioeconomic and health access factors, such as high hospitalization costs, inadequate asthma knowledge, and poor asthma management. [17][18][19][20][21][22][23] Our study suggests the need for further studies of these small minority groups to understand and intervene on asthma outcomes in diverse racial/ethnic groups. 1.0 (1.0-1.0) 1.0 (1.0-1.0) 0.9 (0.9-0.9)…”
Section: Discussionmentioning
confidence: 99%
“…15 Other studies also found a higher burden of asthma among AI/AN and/or Filipino children, with multiple underlying socioeconomic and health access factors, such as high hospitalization costs, inadequate asthma knowledge, and poor asthma management. [17][18][19][20][21][22][23] Our study suggests the need for further studies of these small minority groups to understand and intervene on asthma outcomes in diverse racial/ethnic groups. 1.0 (1.0-1.0) 1.0 (1.0-1.0) 0.9 (0.9-0.9)…”
Section: Discussionmentioning
confidence: 99%
“…2010;36(1): [8][9][10][11][12][13] appropriate and intelligible to the target population, similar to questionnaires validated for use in other countries. (10,11,15) The questionnaire meets the criterion of content/face validity.…”
Section: Discussionmentioning
confidence: 99%
“…However, translating a questionnaire is difficult, and such a translation might not be suitable for all populations, since medical terminology and practices, as well as knowledge about asthma, differ among populations. (11)(12)(13)(14) Brazil is a large country with five distinct regions (southern, southeastern, central-west, northeastern, and northern), each with distinct habits and cultures. In order to avoid regional biases, experts from all regions were consulted so that the questionnaire would be suitable for all patients in Brazil.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Healthy Public Housing Initiative partnered with the Boston Housing Authority to implement policy and sustainable programs to reduce exposure to asthma triggers in public housing units in Boston. The Boston Chinatown Asthma Studies (36,(43)(44)(45) developed asthma terminology that previously did not exist in Cantonese and improved communication with asthma-affected families. For almost 2 decades, Community Action Against Asthma (46-51) has led CBPR initiatives to enhance understanding of asthma in low-income neighborhoods in Detroit and has implemented programs that reduce indoor asthma triggers; it is currently is investigating the effects of outdoor triggers such as vehicle emissions and exposure to highways.…”
Section: Addressing Pulmonary Health Disparitiesmentioning
confidence: 99%